Narrating Europe's Migration and Refugee 'Crisis'. Issue 2 (July 2016) - Collyer, Michael; King, Russell
It is very clear – as many journalists covering the unfolding migration and refugee crisis have pointed out – that geography lies at the heart of the events taking place in Europe and the Mediterranean. It is a story of borders and routes, of distance and proximity, and of location and accessibility. The role of (re-) bordering has been fundamental in states' attempts to 'manage' and 'control' the refugee and migrant flows and, in this respect, we observe a return to the more traditional practices of bordering – physical barriers and personnel-heavy security controls – rather than the previous processes of 'externalizing' and 'internalizing' border management. In the Eastern Mediterranean and the Balkans the external border of the European 'fortress' has been prised open, whilst the free-movement ethos of the Schengen area has been compromized by EU states' reactions to the large-scale movement of migrants and refugees and recent acts of terrorism. In this introductory paper we bring a critical geopolitical lens into play in order to understand the European, regional and global power geometries at work, and we critically examine the political and media rhetoric around the various discursive constructions of the migrant/refugee 'crisis', including both the negative and the Islamophobic utterances of some European leaders and the game-changing iconicity of certain media images.